Konsep Sikap Bijaksana sebagai Bentuk Pengendalian Emosi dalam Perspektif Taoisme - Riyani, Nidya Ulfa (Jurnal Riset Agama, 2022)
Emotions greatly affect human behavior because humans express themselves through emotions. Emotionally capable humans can understand, know, and handle feelings well. On the other hand, a wise attitude is able to guide a person in dealing with various and complicated life circumstances. This research aims to discuss the teachings of wisdom, especially in Taoism. This research uses qualitative method through literature study. The primary data used is a book entitled "A Translation of Lao Tzu's Tao Te Ching and Wang Pi's Commentary" which was translated by Paul J. Lin. The secondary data used as support is an article entitled "Unsur-unsur Filsafat Manusia yang Terkandung dalam Pemikiran Filsafat Cina dan Manfaatnya bagi Peningkatan Sumber Daya Insani" written by Lasiyo. The findings of this research show that according to Taoism, wisdom is an attitude that is simple, gentle, natural, humble, and surrenders to the way of the universe. The conclusion of this research is that Taoism is an ancient philosophy that is practical and focuses on human life. Emotional control contained in the teachings of Taoism includes a wise attitude that relies on the role of intuition, passive, and pessimistic by always accepting all things that happen.